Effects of Beta-Glucan on Performance of Broiler Rabbits - Martin Fik; Henrieta Arpášová; Cyril Hrnčár (Scientific Papers Animal Science and Biotechnologies, 2023)
An experiment was conducted in order to evaluate the effects of beta glucan on selected breeding properties of broiler rabbits. The goal was to compare the results in two groups of animals, which were administered different beta glucan doses, during a period of time between weaning (day 42 after the birth) and day 84 after the birth. Control group K was administered per oral suspension of Sulfacox, preparation against coccidiosis. Experimental group E1 was served a per oral water suspension of beta glucan powder, in concentration 5 g/L for every 5 kg of body weight. Experimental group E2 was served a per oral water suspension of beta glucan powder, in concentration 10 g/L for every 5 kg of body weight. At day 84 after the birth, control group C average body weight was 2515.75g, compared to 2459.88g in group E1 and 2455.77g in group E2. Two mortalities were noted in control group C between day 49 and 63, compared to two mortalities in group E1 and one mortality in group E2 during the same period of time. In all cases, coccidiosis was the reason for mortalities. In all animals, no statistically significant differences in selected breeding properties were observed.